EDUKASI GIZI SEIMBANG DAN MAKANAN JAJANAN SEHAT DI SDN 39 PASAR AMBACANG KOTA PADANG - Putri Aulia Arza; Yeffi Masnarivan; Risti Kurnia Dewi; Fitriyani Fitriyani; Dhiya Fahdila Rahmah; Afifah Khairani Ananda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Consumption of food with balanced nutrition and consumption of food that is safe for school children is important to be concerned about because it greatly impacts the health of children. SDN 39 Pasar Ambacang is one of the primary schools in Kuranji District, Padang City. Based on the results of direct observation about schools, PJAS is quite widely available. Such as PJAS published by school children such as colorful syrup ice, fried sausages / grilled and fried / grilled meatballs. Observation of the nutritional status of school children in SDN 39 Pasar Ambacang there are some obese children and some are very thin and small. The purpose of this community service is to increase school children's knowledge about healthy snacks and balanced nutrition. The method is conducting nutrition education and evaluating increasing students' knowledge using a questionnaire. This event starts with introduction and starts with a pre test. The next activity is nutrition education consisting of materials and simulations in preparing a balanced nutritional menu and choosing healthy snacks with a model of food media, post-test, and question and answer prizes with community service participants. Participants were enthusiastic in participating in the activity. From the pre-test and post-test results it was concluded that there were significant differences between the level of knowledge before and after nutrition education.